THE FACTORS EFFECTING FIRM PERFORMANCE EVIDENCE FROM INDONESIA - Mishael, Audi; Wijaya, Henryanto (International Journal of Application on Economics and Business, 2025)
This study aims to validate and quantify the simultaneous and partial effects of Intellectual Capital, Firm Size Liquidity, on Financial Performance in real estate and property companies, based on the Indonesia Stock Exchange (IDX) 2021-2023 as a limitation field. This study uses a data processing method with the EViews version 12 application. This research determined 120 observational data that were taken using purposive sampling method with a total of 40 companies. The data used in this research is secondary data, collected through a literature review. The results show that Intellectual capital and Liquidity has a negligible impact on the Financial Performance, while firm size has a positive and substantial impact on the Financial Performance. Therefore, it can be inferred that Firm Size are accepted and Intellectual Capital and Liquidity is rejected.